Vortex kinks in superconducting films with periodically modulated thickness - Facio, Jorge I.; Abate, Anabella; Guimpel, Julio; Cornaglia, Pablo S.; Fasano, Yanina; Guimpel, Julio; Fasano, Yanina (IOP Publishing, 2013)
Fil: Facio, Jorge I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina